2016
DOI: 10.1515/ijamh-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Examination of YouTube videos related to synthetic cannabinoids

Abstract: The popularity of synthetic cannabinoids (SCBs) is increasing the chance for adverse health issues in the United States. Moreover, social media platforms such as YouTube that provided a platform for user-generated content can convey misinformation or glorify use of SCBs. The aim of this study was to fill this gap by describing the content of the most popular YouTube videos containing content related to the SCBs. Videos with at least 1000 or more views found under the search terms “K2” and “spice” included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
0
18
0
1
Order By: Relevance
“…As regards the second aim of this study, regarding analysing the characteristics of the audiovisual material, the videos about drugs, and in the absence of a qualitative study which looks deeper into the content, these videos offer a more suitable format for the adolescent audience as their audiovisual material shows private spaces to a lesser extent, there are less cases of children appearing without their identities being protected and they also stand out due to their positive focus. In any case, it would be advisable to look into this issue in more depth, given the characteristics of videos on these topics (Fullwood et al, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the second aim of this study, regarding analysing the characteristics of the audiovisual material, the videos about drugs, and in the absence of a qualitative study which looks deeper into the content, these videos offer a more suitable format for the adolescent audience as their audiovisual material shows private spaces to a lesser extent, there are less cases of children appearing without their identities being protected and they also stand out due to their positive focus. In any case, it would be advisable to look into this issue in more depth, given the characteristics of videos on these topics (Fullwood et al, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This is a relevant subject. As noted in Fullwood, Kecojevic, and Basch (2016), in connection with synthetic cannabinoids it is observed that, in spite of YouTube's potential as a surveillance tool to fight the epidemic (in the case of the USA), most of the videos related to this theme are uploaded by consumers and are videos describing, encouraging and promoting drug use. Be that as it may, this phenomenon encourages different institutions and authorities to create and disseminate informational videos which take into account at a theoretical and practical level the options of changing behaviour on health issues.…”
Section: Subthemesmentioning
confidence: 99%
“…Other studies pointed to social media as a potential source of information that illegally promotes the sale of controlled prescription drugs directly to consumers [66]. In the case of cannabinoids, there was often content that described, encouraged, promoted [54], or even normalized the consumption of illicit substances [70].…”
Section: Drugs and Smokingmentioning
confidence: 99%
“…Various authors conclude that the Internet is not a reliable source of information and does not accurately inform patients about coronary heart disease [28], cardiac murmurs [29], varicose veins and the treatment options [30], gastric cancer [31], breast cancer [32,33], head and neck cancers [34], oral cancer [35], prostate cancer [36], urological oncology [37], hemangiomas [38], menopause [39], diabetes mellitus [40,41], parathyroid disease [42], healthy nutrition [43,44], vitamin B12 [45], depression [46], epilepsy [47] rheumatological conditions [48], osteoporosis [49], first aid for burns [50,51], first aid in choking [52], cervical and lumbar disc herniation [53,54], scoliosis [55], vascular and other surgical operations [56,57], influenza [58], child fever [59], coeliac disease [60]. The concerns regarding the poor quality and many times even misguided health-related information available on the Internet have increased with the advent of Web 2.0 and its equivalents in the medical field (health blogs, health-oriented social media groups, YouTube), namely Health 2.0 and Medicine 2.0, which are characterized, among other traits, by an unprecedented increase in user-provided content [61][62][63].…”
Section: The Internet As a Source Of Health-related Information The Hmentioning
confidence: 99%